Pengembangan TBM Karya Mulya Melalui Aplikasi Teknologi dan Konsep Literasi Informasi - Ningsih, Putri Setia; Misroni, Misroni (Librarianship in Muslim Societies, 2023)
The development of community reading parks through the application of technology and Information Literacy concepts has become a significant effort in promoting literacy and access to knowledge within the community at large. This effort is necessary to utilise the principles of technology and information literacy to improve reading experience and knowledge dissemination. This research discusses the implementation of information literacy in the library of Karya Mulya community reading park. The purpose of this study is to describe the development of Taman Baca Masyarakat (TBM) Karya Mulya through the application of technology and the concept of Information Literacy through an activity programme created by academic supervisors of lecturers and students. This research was conducted using a qualitative approach with a case study method. Data collection was done through observation and interviews with TBM managers. The results of this study indicate that the development of TBM Karya Mulya through the application of technology and the concept of Information Literacy is designed in addition to supporting one of its parent programmes, namely TBM Karya Mulya, also to introduce the concept of information literacy to TBM managers. The implementation of the programme consists of several types of activities such as the installation of SLiMS, E-DDC, and the classification of unnumbered books for stored books as well as introducing the concept of information literacy to students.  This activity has enriched the understanding of information literacy among visitors to Taman Bacaan Masyarakat Karya Mulya, especially students and lecturers who were previously unfamiliar with the concept of information literacy.